Atlas of Global Change Risk of Population and Economic Systems (IHDP/Future Earth-Integrated Risk Governance Project Series, 2022)
This book is open access and illustrates the spatial distribution of the global change risk of population and economic systems with the maps of environment, global climate change, global population and economic systems, and global change risk. The risks of global change are mapped at 0.25 degree grid unit. The risk results and their contribution rates of the world at national level are unprecedentedly derived and ranked. The book can be a good reference for researchers and students in the field of global climate change and natural disaster risk management, as well as risk managers and enterpriser to understand the global change risk of population and economic systems.